Strange and ever after - Dennard, Susan (Dennard, Susan. Something strange and deadly trilogy., 2014)
"Traveling to Egypt with the Spirit-Hunters, Eleanor Fitt must control her growing power, face her feelings for Daniel, and confront the evil necromancer Marcus--all before it's too late"--